C. Dué. Homeric Variations on a Lament by Briseis . Greek Studies: Interdisciplinary Approaches, Series Editor: G. Nagy, Harvard University, Rowman and Littlefield Publishers, Inc. Lanham, 2002, xi+141 pp. - Zecchin de Fasano, Graciela Cristina (2003)
Fil: Zecchin de Fasano, Graciela Cristina. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.